Macrophage-Osteoclast Associations: Origin, Polarization, and Subgroups - Sun, Yang; Li, Jiangbi; Xie, Xiaoping; Gu, Feng; Sui, Zhenjiang; Zhang, Ke; Yu, Tiecheng (Frontiers in Immunology, 2021)
Cellular associations in the bone micro-environment are involved in modulating the balance of bone remodeling and resorption, which is necessary for keeping normal bone morphology. Macrophages and osteoclasts are both important components of the bone marrow and make a significant contribution to the associations. Macrophages could interact with osteoclasts and regulate bone metabolism by secreting a variety of cytokines. Recent studies have fully explored either macrophages or osteoclasts, but little has been talked about their associations. Elucidating the associations between macrophages and osteoclasts in normal and pathological states is of great significance. Therefore, this paper reviews this topic from three novel aspects of the origin, polarization and subgroups based on the previous work, to provide a reference for subsequent research and treatment of bone-related diseases.